Ferrocement laminate strengthens RC beams - Al-Kubaisy, M.A.; Jumaat, Mohd Zamin (Concrete International, 2000)
Repairing and strengthening reinforced concrete elements can be accomplished in several ways: epoxy injections, patch repair, steel place bonding, post-tensioning, encasement of additional reinforcement and the fiber-reinforced plastic technique. Each of these methods comes with it's own associated problems and engineers and researchers have looked for alternative methods. The authors of this article present the results of their tests of ferrocement as the repair and strengthening material. The articles provides the details of their experimental program, the materials tested and the results they found. Overall, the use of ferrocement can increase the ultimate strength of reinforced concrete significantly.